2002
DOI: 10.1054/math.2001.0431
|View full text |Cite
|
Sign up to set email alerts
|

Manual examination of accessory movements–seeking R1

Abstract: Movement diagrams are used by physiotherapists to depict the behaviour of resistance through the available range of accessory and physiological joint movement. It is generally accepted that for an asymptomatic joint, the resistance first felt by the therapist (R1) occurs towards the end of range. R1 is considered to be at the transition point between the toe and linear region of a load displacement curve. The aim of this study was to more accurately define R1 from force displacement curves of accessory movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 21 publications
1
26
0
8
Order By: Relevance
“…Provavelmente, a força solicitada pelo examinador B para mobilizar a articulação talocrural foi menor quando comparado ao examinador A. Este efeito pode ser observado nos dados representados na tabela 1. Segundo alguns autores, a força aplicada durante a manobra de mobilização, grau III e IV de Mailtand é exercida contra uma resistência mínima e aumentada gradativamente até encontrar uma resistência máxima 8,13,16 , promovendo assim uma deformação viscoelástica dos tecidos periarticulares 17 .…”
Section: Fminunclassified
“…Provavelmente, a força solicitada pelo examinador B para mobilizar a articulação talocrural foi menor quando comparado ao examinador A. Este efeito pode ser observado nos dados representados na tabela 1. Segundo alguns autores, a força aplicada durante a manobra de mobilização, grau III e IV de Mailtand é exercida contra uma resistência mínima e aumentada gradativamente até encontrar uma resistência máxima 8,13,16 , promovendo assim uma deformação viscoelástica dos tecidos periarticulares 17 .…”
Section: Fminunclassified
“…If a relationship exists with lighter force application and greater accuracy, this would be consistent with the findings of Tuttle et al, 9 whose work indicated the end point of the force-displacement curve during PIVM is not as critical diagnostically as the midrange. The concept of using increased palpatory resistance to PA pressure to represent pathology is supported by the work of multiple investigators, 48,49 which demonstrates increased resistance being associated with symptomatic levels. These investigators showed that changes in the early to middle portions of the force-displacement curves were more revealing than the end points in identifying symptomatic levels.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators showed that changes in the early to middle portions of the force-displacement curves were more revealing than the end points in identifying symptomatic levels. 49 This would appear to challenge long held beliefs about the end point of passively delivered movement in the spine being of greatest importance in describing mechanical lesions. The benefit of force feedback in learning manual skills has already been demonstrated with improved reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In the wrist joint, accessory movement of the carpal bones occurs against the radius during extension (dorsiflexion) -flexion (palmar-flexion) motion. A number of previous studies have described changes in the patterns of carpal bone movement during wrist motion [2][3][4][5][6][7][8][9][10][11][12][13][14] , some of which have specifically examined the motion of the lunate during wrist extension-flexion [2][3][4] . Moojen et al 2) reviewed the contribution of the scaphoid and the lunate to the inplane motion during flexion-extension of the wrist.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known, however, about normal carpal bone motion in the palmar-dorsal direction during flexion-extension motion 4) . In one of the few such studies, Petty et al 5) investigated the force-displacement curve of accessory movement that occurs in the radiocarpal joint.…”
Section: Introductionmentioning
confidence: 99%